Multicomponent biological terms of secondary nomination (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with multi-biological terms secondary category. Within threecomponental biological terms specifically mentioned four structural and semantic types: «adjective + adjective + noun», «adjective + noun + adjective», «noun + adjective + noun», «adjective + noun + noun». It was found that biological chotyrychlenni terminospoluchennya among multi-terms are a minority.
Keywords: secondary nomination; analytical terms; a component of figuratively; a component of direct value